(untitled) (INNOVATIVE ECONOMY, 2020)
Danylenko-Kulchytska V.A., Nahara M.B. MARKETING COMMUNICATIONS OF TOURIST ENTERPRISES: SYSTEM AND MANAGEMENT ASPECTS Purpose. The aim of the article is to determine the marketing communications system at tourist enterprises, to define its complementary components and, in particular, to study the features and effectiveness of tourism services advertising Methodology of research. General scientific and special methods were used in the process of research. Systems analysis is used for disclosure of basic categories. Methods of analysis and synthesis were used in substantiating the process of creating and maintaining a travel company page in a social network. Methods of observation and logical generalization were used in considering the features of social networks for tourist services promotion. Findings. It is established that the system of marketing communications of the tourist enterprise is a dynamic set of interrelated processes based on the integrated purpose approach to the activity of the tourist enterprise in order to establish the development priorities, taking into account the resource, human and marketing potential of the enterprise. It is established that in recent years, among the defining requirements of the long-term success of a tourist enterprise is the need for marketing orientation. That is why finding a communication idea, defining mission, values and vision have become the defining conditions for the successful operation of tourist industry enterprises. Numerous types of marketing communications are written in the literature, and their actual use is made up of informal and informal subdivisions, departments of the company, and marketing malls. It is determined that the most actual remains the task of developing and implementing the latest tools of marketing communication and their integration into the management processes of tourist enterprises. Originality. It is determined that system of marketing communications of tourism enterprise is a dynamic set of interrelated processes based on integral approach to tourism enterprise activity. Its aim is to establish priorities of development, taking into account resources, human and marketing potential of the company. Practical value. The results of the research will contribute to the continuous growth of the number of clients and, accordingly, the successful functioning of the tourism organization in the market. Key words: tourism, tourism services, marketing communications, communication channels, marketing system, social network, advertising, travel company.